Using craniofacial characteristics to predict optimum airway pressure in obstructive sleep apnea treatment - Cunha,Thays Crosara Abrahão (2020)
Abstract Introduction: Manual titration is the gold standard to determinate optimal continuous positive airway pressure, and the prediction of the optimal pressure is important to avoid delays in prescribing a continuous positive airway pressure treatment. Objective: To verify whether anthropometric, polysomnographic, cephalometric, and upper airway clinical assessments can predict the optimal continuous positive airway pressure setting for obstructive sleep apnea patients. Methods: Fifty men between 25 and 65 years, with body mass indexes of less than or equal to 35 kg/m2 were selected. All patients had baseline polysomnography followed by cephalometric and otolaryngological clinical assessments. On a second night, titration polysomnography was carried out to establish the optimal pressure. Results: The average age of the patients was 43 ± 12.3 years, with a mean body mass index of 27.1 ± 3.4 kg/m2 and an apnea-hypopnea index of 17.8 ± 10.5 events per hour. Smaller mandibular length (p = 0.03), smaller atlas-jaw distance (p = 0.03), and the presence of a Mallampati III and IV (p = 0.02) were predictors for higher continuous positive airway pressure. The formula for the optimal continuous positive airway pressure was: 17.244 − (0.133 × jaw length) + (0.969 × Mallampati III and IV classification) − (0.926 × atlas-jaw distance). Conclusion: In a sample of male patients with mild-to-moderate obstructive sleep apnea, the optimal continuous positive airway pressure was predicted using the mandibular length, atlas-jaw distance and Mallampati classification.